Analysis of Chinese-English Code-mixing among Undergraduates in Colleges: A Case Study of Qianjiang College - Liao, Binyan (International Journal of Linguistics, Literature and Translation, 2022)
With the increasing trend of globalization and closer ties between China and Western countries, more and more Chinese people can use English for daily communication. Thus, the phenomenon of Chinese-English code-mixing is becoming more and more common, especially among college students. Based on a questionnaire survey among 218 undergraduates of Qianjiang College of Hangzhou Normal University, this paper tries to analyze the characteristics and reasons for Chinese-English code-mixing on campus and explore the individual preference and tolerance for it so as to reveal the influence of the phenomenon on the study and growth of undergraduate college students and meanwhile obtain a deeper understanding of code-mixing in bilingual practices. The research findings show that college students hold an affirmative attitude towards Chinese-English code-mixing and in the aspect of their preference and tolerance for it, there exist some differences between English majors and non-English majors.